The Influence of Internship Experience and Work Motivation on Work Readiness in Vocational Students: PLS-SEM Analysis - Sidiq Supriyanto; Sudji Munadi; Rihab Wit Daryono; Yayan Adrianova Eka Tuah; Muhammad Nurtanto; Shilmi Arifah (Universitas Muhammadiyah Surakarta, 2023)
Internships have an important role in the experience, application, and development of student's skills. The implementation of the internship has not been maximally achieved because students have not been given full assignments due to a lack of work skills, self-confidence, and work motivation. This study aims to reveal the effect of internship experience and work motivation on work readiness. Sampling used a random sampling technique and obtained a sample of 94 students of class XI automotive engineering at 5 vocational schools in Yogyakarta. The combination of factor analysis and regression analysis was used to analyze the data using second-order PLS-SEM analysis. The evaluation of the measurement model has met the requirements of the convergent validity test at the outer loading of ≥0.70 and AVE ≥0.50. The discriminant validity has met the requirements of the Fornell-Larcker test. Internal consistency reliability meets the requirements of CA, rho_A, and CR with a score of 0.70. Evaluation of the structural model shows the value of effect size (f2) with a large effect, the determination coefficient (R2) of the variable is 76.20%, and the predictive relevance (Q2) is 58.00%. Hypothesis testing is based on the β-coefficient, ρ-value, dan T-statistic values that have met the cut-off values suggested in the literature. So that all hypotheses Ha is accepted which indicate that there is a positive and significant effect on the internship experience and motivation on student work readiness. There needs to be better efforts to improve internship experience and work motivation so that guidance and supervision from supervising teachers must always be given so that work readiness is more optimal.